Passive and Adaptive Damping Systems for Vibration Mitigation and Increased Fatigue Service Life of a Tied Arch Railway Bridge. (14th November 2014) - Andersson, Andreas; O'Connor, Alan; Karoumi, Raid
Abstract In this article, the use of external damping systems for vibration mitigation of railway bridge dynamics is studied. For a presented case study bridge, the performance of different tuned mass damper systems (TMDs) is studied. During train passage, the change in dynamic characteristics of the bridge may produce a significant detune to a passive TMD. Therefore, routines for a variable stiffness TMD using incremental frequency estimates are developed. Based on numerical simulations, the cumulative fatigue damage is calculated for different damper systems. Due to resonant behavior, the results are found to highly depend on the train speed. Based on an assumed probability density function for the train speed, fragility curves are produced to express the probability of fatigue failure as a function of the number of train passages.